A low intensity, community based lifestyle programme to prevent weight gain in women with young children: cluster randomised controlled trial. (13th July 2010) - Lombard, Catherine; Deeks, Amanda; Jolley, Damien; Ball, Kylie; Teede, Helena
Abstract : Objective To develop and evaluate the effectiveness of a community behavioural intervention to prevent weight gain and improve health related behaviours in women with young children. Design Cluster randomised controlled trial. Setting A community setting in urban Australia. Participants 250 adult women with a mean age of 40.39 years (SD 4.77, range 25-51) and a mean body mass index of 27.82 kg/m 2 (SD 5.42, range 18-47) were recruited as clusters through 12 primary (elementary) schools. Intervention Schools were randomly assigned to the intervention or the control. Mothers whose schools fell in the intervention group (n=127) attended four interactive group sessions that involved simple health messages, behaviour change strategies, and group discussion, and received monthly support using mobile telephone text messages for 12 months. The control group (n=123) attended one non-interactive information session based on population dietary and physical activity guidelines. Main outcome measures The main outcome measures were weight change and difference in weight change between the intervention group and the control group at 12 months. Secondary outcomes were changes in serum concentrations of fasting lipids and glucose, and changes in dietary behaviours, physical activity, and self management behaviours. Results All analyses were adjusted for baseline values and the possible clustering effect. Women in the control group gained weight over the 12 month study period (0.83 kg, 95% confidence interval (CI) 0.12 to 1.54), whereas those in the intervention group lost weight (−0.20 kg, −0.90 to 0.49). The difference in weight change between the intervention group and the control group at 12 months was −1.13 kg (−2.03 to −0.24 kg; P<0.05) on the basis of observed values and −1.11 kg (−2.17 to −0.04) after multiple imputation to account for possible bias created by missing values. Secondary analyses after multiple imputation showed a difference in the intervention group compared with the control group for total cholesterol concentration (−0.35 mmol/l, −0.70 to −0.001), self management behaviours (diet score 0.18, 0.13 to 0.33; physical activity score 0.24, 0.05 to 0.43), and confidence to control weight (0.40, 0.11 to 0.69). Regular self weighing was associated with weight loss in the intervention group only (−1.98 kg, −3.75 to −0.23). Conclusions Weight gain in women with young children could be prevented using a low intensity self management intervention delivered in a community setting. Self management of health behaviours improved with the intervention. The response rate of 12%, although comparable with that in other community studies, might limit the ability to generalise to other populations. Trial registration Australian New Zealand Clinical Trials Registry number ACTRN12608000110381.